Evaluation of a group webinar and individual video-conferencing support program designed to upskill staff working with children with autism in regional and remote areas. Issue 2 (30th November 2020) - Johnsson, Genevieve; Lincoln, Michelle; Bundy, Anita C.; Costley, Debra; Bulkeley, Kim
Abstract : Purpose: The rollout of individualised disability funding in Australia resulted in an increased demand for services for people with a disability, particularly support for the high percentage of Australians with autism spectrum disorder. Continuing professional development is one way to grow and maintain a skilled workforce; however, face-to-face opportunities can be limited in remote areas of Australia. Technology may provide a low-cost and widely accessible platform for providing education and support for staff in these areas. Design/methodology/approach: The current study evaluated a novel webinar training and individual online support program for 36 allied health, education and community support staff. Data were collected via a survey on changes in perceived "knowledge and skills" and "confidence" in supporting children with autism, as well as mode of participation, and accessibility of the program. Findings: Participants reported a significant increase in their "knowledge and skills" and "confidence", in working with children with autism. This increase was positively related to the number of webinars the participants accessed. The mode of webinar access was predominantly via watching recordings of webinars (asynchronous learning). Synchronous learning via individual online sessions was accessed by a small number of participants, mostly allied health professionals. Workload and scheduling were identified as barriers to engaging in the program. The technology platform was found to be accessible and acceptable. Originality/value: A predominantly asynchronous mode of delivery was successful, thereby increasing program access and flexibility for remote staff. Technology was not a barrier to accessing the program regardless of remoteness or job role.